Life-history traits of the Miocene Hipparion concudense (Spain) inferred from bone histological structure. - Cayetana Martinez-Maza (PLoS ONE, 2014)
Histological analyses of fossil bones have provided clues on the growth patterns and life history traits of several extinct vertebrates that would be unavailable for classical morphological studies. We analyzed the bone histology of Hipparion to infer features of its life history traits and growth pattern. Microscope analysis of thin sections of a large sample of humeri, femora, tibiae and metapodials of Hipparion concudense from the upper Miocene site of Los Valles de Fuentidueña (Segovia, Spain) has shown that the number of growth marks is similar among the different limb bones, suggesting that equivalent skeletochronological inferences for this Hipparion population might be achieved by means of any of the elements studied. Considering their abundance, we conducted a skeletechronological study based on the large sample of third metapodials from Los Valles de Fuentidueña together with another large sample from the Upper Miocene locality of Concud (Teruel, Spain). The data obtained enabled us to distinguish four age groups in both samples and to determine that Hipparion concudense tended to reach skeletal maturity during its third year of life. Integration of bone microstructure and skeletochronological data allowed us to identify ontogenetic changes in bone structure and growth rate and to distinguish three histologic ontogenetic stages corresponding to immature, subadult and adult individuals. Data on secondary osteon density revealed an increase in bone remodeling throughout the ontogenetic stages and a lesser degree thereof in the Concud population, which indicates different biomechanical stresses in the two populations, likely due to environmental differences. Several individuals showed atypical growth patterns in the Concud sample, which may also reflect environmental differences between the two localities. Finally, classification of the specimens' age within groups enabled us to characterize the age structure of both samples, which is typical of attritional assemblages.